Double-blind Randomized Placebo-controlled Clinical Trial of Omega 3 Fatty Acids for the Treatment of Diabetic Patients With Nonalcoholic Steatohepatitis. Issue 2 (February 2015) - Dasarathy, Srinivasan; Dasarathy, Jaividhya; Khiyami, Amer; Yerian, Lisa; Hawkins, Carol; Sargent, Ruth; McCullough, Arthur J.
Abstract : Background: Nonalcoholic steatohepatitis (NASH) is common and severe in patients with diabetes mellitus. Although, there are no effective treatments for NASH in diabetic patients, preliminary reports suggest that polyunsaturated fatty acids (PUFA) may be beneficial in these patients. Aim: A prospective, randomized, double-blind placebo-controlled study (NCT 00323414) was performed in NASH patients with diabetes. Clinicaltrials.gov (NCT 00323414). Subjects and Methods: A total of 37 patients (50.6±9.8 y) with well-controlled diabetes (HbA1C<8.5%) were randomized to receive either PUFA containing eicosapentaenoic acid (2160 mg) and docosahexaenoic acid (1440 mg) daily or an isocaloric, identical placebo containing corn oil for 48 weeks under CONSORT guidelines. Clinical, demographics, biochemical laboratory tests, body composition using DEXA, and liver biopsy were performed at randomization and at the end of treatment. Liver biopsy was scored by the NASH CRN criteria. An intention-to-treat analysis was performed. Results: At inclusion, sex, age, body weight, biochemical tests, glucose control, and liver histology were similar in the 2 treatment groups. There was no change in liver enzymes, body weight, or body composition during the study in either group. At the end of the treatment, hepatic steatosis and the activity score improved ( P <0.05) and lobular inflammation worsened ( P <0.001) with placebo but was unchanged with PUFA. At the end of the treatment, insulin resistance (serum glucose and HOMA) worsened with PUFA but not placebo. Conclusions: PUFA provided no benefit over placebo in NASH patients with diabetes. The effects of PUFA on histology and insulin resistance were inferior to placebo. These data provide no support for PUFA supplements in NASH. Abstract : Supplemental Digital Content is available in the text.